Wingless Angels: Homer as an Authoritative Historical and Aesthetic Source in Early Modern Period - Riklius, Tomas (Literatūra, 2021)
This paper discusses the unusual reference to Homer in Federico Borromeo’s De pictura sacra in which Homer is quoted as an authoritative aesthetic and historical source to justify the depiction of wingless angels by Michelangelo. It is said that the great Greek poet represented the gods without wings as if they could move with their feet joined together. The first part of the article examines this relatively obscure remark and its possible sources. One of the reasons for such a quotation is the general Renaissance attitude towards Classical texts to provide a historical perspective and establish an authoritative argumentation. However, a closer analysis discloses that Borromeo refers to Homer not simply as an aesthetic and historical but as a quasi-theological source of God-inspired wisdom.
Keywords: Homer; early modern period; humanism; art theory; art treatises; Federico Borromeo